Implementation Of Accrual-Based Accounting System At Gomo Sub-District Office, Gomo District, South Nias Regency - Titus Desman Hia; Dedi Irawan Zebua; Serniati Zebua; Sophia Molinda Kakisina (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine the implementation of the accrual-based accounting system at the Gomo Sub-District Office and to identify the challenges encountered in its application. A descriptive qualitative method was employed, with data obtained through interviews, observations, and documentation.The results show that the accrual-based accounting implementation has complied with Government Regulation No. 71 of 2010, and the financial reports produced meet the criteria of relevance, reliability, comparability, and understandability. However, challenges such as limited human resources, lack of training, and inadequate supporting facilities remain.In general, the implementation is satisfactory but still requires strengthening staff capacity and optimizing financial information systems to achieve more transparent, accountable, and useful financial reporting for decision-making.